Penerapan Metode Continous Review System dalam Proses Pengendalian Bahan Baku Karet Guna Meminimalkan Stock - Akbar, Muhammad Ghany; Nuha, Hilyatun; Purnama, Jaka (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
PT Putrasean Rubber Industri faces recurring shortages of brown rubber, which lead to stock outs, production delays, and increased inventory costs. This study aims to apply the Continuous Review System (CRS) method to improve raw material inventory control, minimize shortages, and reduce total inventory costs. The research uses production, demand, lead time, ordering cost, holding cost, and shortage cost data from September 2024 to August 2025. The CRS method is analyzed through two scenarios—back order and lost sales—and compared with the company’s existing inventory system. The results indicate that CRS provides more accurate calculations of optimal order quantity, safety stock, and reorder point. Furthermore, CRS generates lower total inventory costs compared to the existing method. Overall, the application of CRS is proven to be more efficient in ensuring production continuity and meeting customer demand consistently.